SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0062
|View full text |Cite
|
Sign up to set email alerts
|

Fast NGC: A New On-Line Technique for Fuel Flow Measurement

Abstract: Knowledge of fuel mass injected in an individual cycle is important for engine performance and modelling. Currently direct measurements of fuel flow to individual cylinders of an engine are not possible on-engine or in real-time due to a lack of available appropriate measurement techniques. The objective of this work was to undertake real-time Coriolis fuel flow measurement using GDI injectors on a rig observing fuel mass flow rate within individual fuel injections. This paper evaluates the potential of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…16 The experimental work has demonstrated that while the PSP technique has enabled the detection of individual fuel pulses, further developments are necessary to generate a repeatable flow estimate with low uncertainty. In [24], we describe a first analysis to improve the repeatability of the phase difference calculation in these experiments, by assuming the phase difference is a function of the instantaneous phase.…”
Section: Resultsmentioning
confidence: 99%
“…16 The experimental work has demonstrated that while the PSP technique has enabled the detection of individual fuel pulses, further developments are necessary to generate a repeatable flow estimate with low uncertainty. In [24], we describe a first analysis to improve the repeatability of the phase difference calculation in these experiments, by assuming the phase difference is a function of the instantaneous phase.…”
Section: Resultsmentioning
confidence: 99%